2003
DOI: 10.1101/gr.611403
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Deletion Formation System Based on Tn5 Double Transposition: Use For Making Minimal Genomes and Essential Gene Analysis

Abstract: In this communication, we describe the use of specialized transposons (Tn5 derivatives) to create deletions in the Escherichia coli K-12 chromosome. These transposons are essentially rearranged composite transposons that have been assembled to promote the use of the internal transposon ends, resulting in intramolecular transposition events. Two similar transposons were developed. The first deletion transposon was utilized to create a consecutive set of deletions in the E. coli chromosome. The deletion procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 29 publications
0
43
0
2
Order By: Relevance
“…Further studies using a YmgF-GFP fusion revealed that YmgF is a membranebound protein, although it did not localize to the E. coli septum site, at least when cells were grown in rich medium (N. Buddelmeijer, personal communication). Interestingly, ymgF is located near the minCDE region within the genome of E. coli K-12, yet ymgF seems to be nonessential, as the corresponding chromosomal DNA region can be deleted without affecting cell viability (22). At present, the role of YmgF in cell division remains elusive, but as this polypeptide interacted specifically with several Fts proteins, one may speculate that it may be involved in the fine tuning of E. coli cell division.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies using a YmgF-GFP fusion revealed that YmgF is a membranebound protein, although it did not localize to the E. coli septum site, at least when cells were grown in rich medium (N. Buddelmeijer, personal communication). Interestingly, ymgF is located near the minCDE region within the genome of E. coli K-12, yet ymgF seems to be nonessential, as the corresponding chromosomal DNA region can be deleted without affecting cell viability (22). At present, the role of YmgF in cell division remains elusive, but as this polypeptide interacted specifically with several Fts proteins, one may speculate that it may be involved in the fine tuning of E. coli cell division.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, when overproduced, YmgF could partially overcome the thermosensitivity of the ftsQ1(Ts) mutant and restore the ftsQ1 viability under lowosmolarity growth conditions. Taken together, these data suggest that YmgF, although previously shown to be not essential for cell viability (6,23,31), might be a novel component of the E. coli cell division machinery.…”
mentioning
confidence: 59%
“…We attempted to further characterize this putative inner membrane-associated protein and, particularly, to examine its potential association with E. coli cell division proteins, although prior reports indicated that the ymgF gene is not essential and could be inactivated without affecting the cell viability (6,23,31). YmgF association with the E. coli cell division machinery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Escherichia coli, the development of genomic engineering techniques utilizing bacteriophage recombinases, homologous recombination, or transposable elements has been reported recently (6,10,12,20,39). By use of such techniques, the construction of a deletion mutant whose genome size was reduced by 1.38 Mb was reported (12).…”
mentioning
confidence: 99%